2022
DOI: 10.1111/bjep.12537
|View full text |Cite
|
Sign up to set email alerts
|

“Teacher, forgive me, I forgot to do it!” The impact of children's prospective memory on teachers' evaluation of academic performance

Abstract: Background According to Munsat (1965, The concept of memory. University of Michigan), a person who makes frequent prospective memory (PM) errors is considered as having a flawed character rather than a bad memory. Given that PM completes its development only in young adulthood, this bias might occur not only within social relationships but also in school. However, little is known about the impact of this bias on academic performance. Aims This study aimed to evaluate the impact of children's PM on teacher's ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In fact, PM develops considerably during childhood, typically reaching its peak only in late adolescence or young adulthood (Zimmermann & Meier, 2006). Considering the negative consequences that frequent forgetting of intentions can have on children's academic success, social relationships, health, and well-being (e.g., Basso et al, 2023;Moeller et al, 2021), researchers have recognized the necessity to investigate ways to support children's PM performance (see Cottini, 2023, for a review of the literature). For instance, recent studies have shown that prompting children to imagine performing the PM task beforehand, namely, giving episodic future thinking (EFT) instructions or asking them to predict their PM performance (i.e., metacognitive monitoring), can improve children's PM performance (Cottini et al, 2018;Kretschmer-Trendowicz et al, 2016.…”
Section: Backgrou N Dmentioning
confidence: 99%
“…In fact, PM develops considerably during childhood, typically reaching its peak only in late adolescence or young adulthood (Zimmermann & Meier, 2006). Considering the negative consequences that frequent forgetting of intentions can have on children's academic success, social relationships, health, and well-being (e.g., Basso et al, 2023;Moeller et al, 2021), researchers have recognized the necessity to investigate ways to support children's PM performance (see Cottini, 2023, for a review of the literature). For instance, recent studies have shown that prompting children to imagine performing the PM task beforehand, namely, giving episodic future thinking (EFT) instructions or asking them to predict their PM performance (i.e., metacognitive monitoring), can improve children's PM performance (Cottini et al, 2018;Kretschmer-Trendowicz et al, 2016.…”
Section: Backgrou N Dmentioning
confidence: 99%
“…In traditional schools, students are taught without collaboration, are expected to accept the teacher's words blindly, and are compelled to learn outdated and impractical theoretical concepts that do not align with their interests and abilities. This outdated educational approach results in poor academic performance and fails to prepare students for lifelong learning (Basso et al, 2023).…”
Section: Introductionmentioning
confidence: 99%